RESPIRATORY COMPLICATIONS FOLLOWING RSV INFECTION IN CHILDREN: FROM ACUTE INFECTION TO PERSISTENT STRUCTURAL SEQUELAE – A LITERATURE REVIEW - Brygida Pinkowicz; Idalia Myszor; Michał Madej; Maria Kubacka; Lucjan Kocemba; Gabriela Mroczka; Sylwia Nycz-Jucha; Paulina Łobaza; Piotr Rachwał; Barbara Nowak-Misiąg (International Journal of Innovative Technologies in Social Science, 2026)
Respiratory syncytial virus (RSV) infections are a significant health burden worldwide, being the leading cause of hospitalization in infants and an important factor affecting long-term lung function. The aim of this review is to provide a summary of current data on the pathophysiological mechanisms, clinical consequences and modern strategies for the prevention of respiratory complications following RSV infection in children. Analysis of the literature indicates that RSV leaves a specific ‘molecular footprint’ in the airways, including both structural changes and activation of ICL2 cells and epigenetic modifications. These phenomena constitute the biological basis for recurrent obstruction and the development of asthma, and the risk of their occurrence is particularly high after a severe course of infection in early infancy. Acute complications such as bronchiolitis, atelectasis or respiratory failure may be associated with a permanent reduction in lung function parameters, persisting even into adulthood. The introduction of modern passive immunoprophylaxis (nirsevimab) and vaccination of pregnant women offers the possibility of protection during the critical developmental window and favorable shaping of the respiratory system development trajectory. RSV remains one of the strongest modifiable risk factors for chronic lung disease, and effective prevention and early identification of risk biomarkers are crucial for protecting the lung function of future generations. Methodology: This article provides a narrative review of the current literature on acute and chronic respiratory complications following RSV infection in children, based on a systematic search and qualitative analysis of available clinical, observational and review studies.